Clinical outcomes of denervation in patients with finger interphalangeal joint arthritis: a retrospective study - Kyung Chul Kim; Sang Hyun Woo (Archives of Hand and Microsurgery, 2026)
Purpose: This study evaluated the clinical outcomes of denervation as an alternative to arthrodesis or arthroplasty in patients with finger interphalangeal joint arthritis refractory to conservative treatment.Methods: A retrospective analysis was performed of 30 joints in 28 patients with distal interphalangeal (DIP) or proximal interphalangeal (PIP) joint arthritis who underwent denervation and had a minimum follow-up of 6 months. Pain was assessed using the visual analog scale (VAS), and functional outcomes were evaluated using the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) score and grip strength ratio (affected/unaffected side). Changes in analgesic medication use were also analyzed.Results: The mean VAS score improved significantly from 5.03 preoperatively to 1.57 at final follow-up (p